Physiological flexibility of free-living aardvarks (Orycteropus afer) in response to environmental fluctuations - Weyer, Nora Marie (My University, 2018)
Aardvarks (Orycteropus afer) are ecological engineers because they dig the burrows that provide shelter for numerous sympatric animals and, as such, are keystone mammals in sub-Saharan Africa. They are nocturnally-active, solitary and elusive. As a result, aardvark ecophysiology is poorly understood, despite their ecological significance. Much of their range is becoming hotter and drier with global climate change, with potential impacts on the aardvarks. A recent drought in the Kalahari in the summer of 2012-13 coincided with high aardvark mortality. The Kalahari semi-desert at the south-western edge of aardvark distribution is the hottest and driest environment currently inhabited by aardvarks. Climate change will likely exacerbate the Kalahari’s harsh conditions through increased aridification and higher environmental temperatures. Whether the physiological plasticity of aardvarks will allow them to buffer such changes is unknown. I therefore studied wild, free-living aardvarks for ~3.5 years (July 2012 to September 2015) at Tswalu Kalahari Reserve, South Africa. Aardvarks were implanted with VHF-tracking units and data loggers to record body temperature and locomotor activity. Camera traps at burrows recorded the aardvarks’ times of emergence. I scored aardvark body condition and collected fresh scats for dietary analysis. Aardvarks typically feed exclusively on ants and termites, which depend largely on vegetation productivity. Thus, I assessed prey abundance and availability monthly using pitfall traps and signs of termite surface activity, and assessed vegetation productivity using field-based transect methods and remote-sensing data (MODIS-EVI). I subsequently measured energy and water content of the aardvarks’ main prey items. Harvester termites (Hodotermes mossambicus) were the most important dietary item for aardvarks throughout the study period, accounting for ~75 % of prey ingested, and providing ~90 % of water and energy needs. By contrast, research in less arid southern African regions found ants to be the dominant dietary item. Although the aardvarks’ regional flexibility in feeding on the most abundant social insects likely improves survival under normal conditions, aardvark well-being in the Kalahari might depend on fluctuations in harvester termite populations. I found that harvester termite abundance correlated with grass availability, which in turn depended on rainfall. During my study, inter-annual variability in rainfall was high; two good rainfall years occurred which had large amounts of rainfall early in the wet season, resulting in high vegetation productivity. During these years, ant (largely in summer) and termite abundances were high, thus aardvarks obtained sufficient prey to cover their minimum daily energy and water requirements, and were in good body condition. Irrespective of the season, aardvarks in good condition remained nocturnal, and were homeothermic, with a low 24-h amplitude of body temperature rhythm (~2.5 °C; varying from 35 to 37.5 °C). Their body temperature rhythm over 24-h closely tracked that of activity, with body temperature increasing at the beginning of the active phase, and declining at the end of the active phase. A drought during summer 2012-13 likely resulted in local declines of termite populations, such that aardvarks were no longer able to meet their energetic requirements. A mass mortality of aardvarks occurred at the end of the summer drought, and surviving aardvarks were in poor condition. Nutritionally-compromised aardvarks relaxed the precision of body temperature regulation, resulting in heterothermy with a high 24-h amplitude of body temperature rhythm, primarily because of low minimum 24-h body temperature (~25 °C). These nutritionally-compromised aardvarks became partly diurnal, some shifting activity entirely to the daytime in the weeks leading up to their deaths. In moribund aardvarks, a dissociation of the 24-h rhythm of body temperature and activity occurred, with minimum 24-h body temperatures occurring during daytime activity, and maximum 24-h body temperature while resting at night. By the winter that followed the summer drought, the late and poor summer rains had not sufficed to ensure a complete recovery of the termite and ant populations at Tswalu. The aardvarks displayed exaggerated heterothermy with 24-h amplitude of body temperature rhythm as high as 11.7 °C, the greatest amplitude ever recorded in a large mammal. During this winter, many aardvarks were in poor body condition and started foraging unusually early, during midday, presumably to compensate for their energetic needs. Some individuals basked in the sun outside their burrows for lengthy periods, thereby passively increasing their body temperature and potentially allowing for savings of up to 7 % of daily energy requirements. However, these energy-saving strategies were not sufficient in all aardvarks to prevent death by starvation, and many more individuals died. This study was the first long-term, and the most comprehensive, study of aardvark diet, behaviour, and thermoregulation in response to prey availability to date. To my knowledge, it was also one of the first studies to record physiological variables in a free-ranging large mammal over a period of more than one year, thereby allowing the assessment of physiological flexibility of aardvarks in response to seasonal and annual changes in the environment. Moreover, it was the first study identifying termites as the aardvark’s key prey item, and the first to estimate the aardvark’s energetic needs in relation to fluctuating food resources as a result of drought. Records of body temperature and activity patterns provided useful direct indicators of physiological well-being in aardvarks. Vegetation cover was a useful index of termite abundance, and thus aardvark resource availability. Understanding the physiological and behavioural limitations of animals in arid ecosystems is vital for assessing responses to increased environmental stress resulting from current and ongoing climate change. The anticipated increase in the frequency and intensity of droughts will likely result in a decline in grass biomass throughout Africa, impacting on termites and other herbivores. Termite declines were likely the main cause of the Kalahari aardvark mass mortality following the drought in the summer of 2012-13. I advocate that future environmental stressors such as drought-induced lack of resources, brought about by climate change, pose a greater threat to aardvarks than previously thought. Aardvark extirpation in the Kalahari will likely have severe cascading effects on other animals co-using aardvark burrows.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa June 2018.